Reliability of Body Fat Percentage Measurements and Their Impact on Airway Resistance: Does Leptin Play a Significant Role? - Garcia-Herrera, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: The measurement of body fat percentage (%BF) could alert us to potential respiratory problems; however, differences in %BF values have been reported depending on the method used. Therefore, the objectives of this study were to determine whether there are differences in %BF obtained through skinfold measurements (SF) and bioelectrical impedance analysis (BIA), and their correlation with airflow limitation (AFL), and secondly, to observe the relationship between leptin and AFL. Materials and Methods: A cross-sectional study was conducted with 80 participants (40 men and 40 women, aged 18–30 years). Assessments of %BF were made using SF and BIA. Spirometric parameters and pulmonary volumes were measured. Plasma leptin levels were determined using ELISA. Bivariate correlations and gender differences were analyzed. Results: When comparing %BF measured by SF and BIA, no significant differences were found between the two methods in either females or males. Furthermore, in both men and women, there was a direct and significant correlation between %BF obtained through BIA and SF (r = 0.936; r = 0.789, p < 0.001, respectively). Leptin showed a significant correlation with airway resistance (Raw) and specific airway resistance (sRaw) in men (r = 0.506; r = 0.553, p < 0.001, respectively) and women (r = 0.537, p = 0.001; r = 0.489, p = 0.003, respectively). Leptin also showed a significant correlation with %BF measured by both SF and BIA in men (r = 0.675; r = 0.687, p < 0.001, respectively) and women (r = 0.583; r = 0.682, p < 0.001, respectively). Conclusions: BIA and SF offer comparable results in estimating %BF. The significant correlation between leptin, %BF, and FEV1/FVC suggests a possible pathophysiological mechanism mediated by adiposity that could affect pulmonary function even in young and clinically healthy individuals. © 2025 by the authors.